2018
DOI: 10.11604/pamj.2018.29.184.15235
|View full text |Cite
|
Sign up to set email alerts
|

Severe malaria and death risk factors among children under 5 years at Jason Sendwe Hospital in Democratic Republic of Congo

Abstract: IntroductionMalaria is still a major public health concern in the Democratic Republic of Congo. Its morbidity and mortality challenge the actual strategies of the fight agains malaria. This study was aimed to describe the epidemiology, the clinical caracteristics and the risk factors of death associated to severe malaria in the pediatric population under 5 years at Sendwe Hospital of Lubumbashi.MethodsThis analytical retrospective study was conducted in Lubumbashi, in the province of Haut-Katanga. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
4
25
0
3
Order By: Relevance
“…Previous studies have shown that people who are at high risk of mortality due to malaria are pregnant women, children under five years of age, immune-compromised patients, and travelers from non-endemic areas into malaria-endemic regions [9][10][11][12]. Therefore, various studies assessing the efficiency of different strategies for malaria control in the DRC mostly focused on these at-risk groups, especially children under five years of age [13][14][15][16]. Adults were reported to receive more mosquito bites and thereby constitute a potential infectious reservoir [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that people who are at high risk of mortality due to malaria are pregnant women, children under five years of age, immune-compromised patients, and travelers from non-endemic areas into malaria-endemic regions [9][10][11][12]. Therefore, various studies assessing the efficiency of different strategies for malaria control in the DRC mostly focused on these at-risk groups, especially children under five years of age [13][14][15][16]. Adults were reported to receive more mosquito bites and thereby constitute a potential infectious reservoir [17].…”
Section: Introductionmentioning
confidence: 99%
“…The health districts are uneven vis-à-vis the availability of these means for supportive treatment. Finally, other poor prognostic factors such as acute malnutrition [62,72] cannot be suppressed in an emergency. In addition, the disparities between health districts observed in the present study could be partly explained by other health programs.…”
Section: Discussionmentioning
confidence: 99%
“…In low-transmission settings in Africa, it was estimated that on average a person might have 1-3 episodes of malaria infection in a year (20). Also, a severe malaria study nding showed that mortality increased with repeated convulsion (21). With severe recurrent malaria, the chance of repeated convulsion is higher and thus increases in mortality.…”
Section: Introductionmentioning
confidence: 99%